VEGFR2 Promotes Metastasis and PD-L2 Expression of Human Osteosarcoma Cells by Activating the STAT3 and RhoA-ROCK-LIMK2 Pathways - Zheng, Bingxin; Zhou, Chuanli; Qu, Guojian; Ren, Chongmin; Yan, Peng; Guo, Wei; Yue, Bin (Frontiers in Oncology, 2020)
The survival rate of osteosarcoma, the most prevalent primary bone tumour, has not been effectively improved in the last 30 years. Hence, new treatments and drugs are urgently needed. Antiangiogenic therapy and immunotherapy have good antitumour effects in many kinds of tumours. It is hypothesised that there may be a synergistic effect between immune checkpoint inhibitors and antiangiogenic therapy. Nevertheless, its potential mechanism is still unclear. Vascular endothelial growth factor receptor-2 (VEGFR2) expression was detected by immunohistochemistry in 18 paired osteosarcoma tissues. Moreover, we investigated the effects of apatinib treatment and VEGFR2 knockdown on osteosarcoma as well as the relevant underlying mechanism. Immunohistochemistry assays showed that, compared with that in primary osteosarcoma, VEGFR2 expression was higher in lung metastases. VEGFR2 was positively correlated with PD-L2 expression in osteosarcoma lung metastasis. Transwell assays indicated that VEGFR2 inhibition reduced osteosarcoma cell metastatic abilities in vitro. We also demonstrated that VEGFR2 inhibition downregulated the STAT3 and RhoA-ROCK-LIMK2 pathways, thereby attenuating migration and invasion. Additionally, VEGFR2 inhibition targeted STAT3, through which it reduced PD-L2 expression in osteosarcoma cells. VEGFR2 inhibition markedly attenuated osteosarcoma lung metastatic ability in vivo. In this study, we presented the pro-metastatic functional mechanism of VEGFR2 in osteosarcoma. VEGFR2 inhibition exhibits antitumour effects through antiangiogenic effects and inhibition of immune escape, which possibly provides potential clinical treatment for metastatic osteosarcoma.